ANTESEDEN RECOVERY SATISFACTION AND WOM POSITIF - Widyaningrum, Premi Wahyu; Sumarsono, Hadi; Kristiyana, Naning (IMAGE : Jurnal Riset Manajemen, 2021)
The development of online shopping activities was followed by an increase in complaints made by customers against the company. Online shopping is the first to receive the most complaints from consumers. The purpose of this study is to obtain empirical answers about how Perceived Justice can affect Positive Word of Mouth after creating Recovery Satisfaction in the minds of consumers. This study connects the dimensions of Perceived Justice as a benchmark for the creation of Recovery Satisfaction. This research is a development of several previous studies by adding novelty related to the relationship of Recovery Satisfaction to Positive WOM. The population in this study were all students of Muhammadiyah University of Ponorogo who are also e-commerce consumers. The sample in this study were 93 respondents. Data analysis using Generalized Structured Component Analysis (GSCA). The results of this study prove that the application of Perceived Justice in relation to e-commerce consumers will regenerate the attitude of Recovery Satisfaction, which in the end will be a big stimulus for the creation of Positive WOM.